2024
DOI: 10.1038/s41598-023-50223-z
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic fracturing using liquid nitrogen on granite at elevated temperatures: a case study for enhanced geothermal systems in Kazakhstan

Sotirios Nik. Longinos,
Randy Hazlett

Abstract: Cryogenic fracturing using liquid nitrogen (LN2) is a novel stimulation technology that enhances porosity, permeability, and rock-fluid contact area in subsurface formations targetted for geothermal energy extraction. In our experimental study, granite cores collected from the Zhylgyz region in South Kazakhstan were equilibrated at various elevated temperatures before treatments involving LN2 exposure time. Compression, Brazilian, and fracture toughness tests were performed on granite with starting temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…To obtain the freeze-thaw coefficient of a rock sample, the measured compressive strength data of the rock were inserted into Equation (2). The variation in the freeze-thaw coefficient with an increasing number of FTCs is shown in Figure 10.…”
Section: The Mechanical Properties Of the Rock Massmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain the freeze-thaw coefficient of a rock sample, the measured compressive strength data of the rock were inserted into Equation (2). The variation in the freeze-thaw coefficient with an increasing number of FTCs is shown in Figure 10.…”
Section: The Mechanical Properties Of the Rock Massmentioning
confidence: 99%
“…In low-temperature environments, the freeze-thaw cycle of a rock mass can exacerbate the damage, deterioration, and fracture process of the rock mass, further affecting stability and engineering safety [1,2]. Therefore, for research and application in related fields, it is necessary to study the freeze-thaw cycle damage [3], deterioration, and fracture process of joints and rock masses.…”
Section: Introductionmentioning
confidence: 99%
“…In their mechanical experiment, Sandstrom et al [59] found that the quantity of freezing-thawing cycles on rocks influenced the mechanical characteristics and fissures in the material. It should also be mentioned that the LN 2 process, as the waterless hydraulic fracturing method, has been used by different research groups in shale [41,60,61], carbonate [17,62], sandstone [63,64], and granite [65][66][67] rocks with successful results as it initiates the mechanical and physical deterioration of the samples of varying mineralogy and composition. This work explores the changes in pore structure characteristics that are seen in coal samples that are obtained from the Karaganda area after they are exposed to liquid nitrogen (LN 2 ), which is used as a waterless fracturing method for coalbed methane (CBM) reservoirs.…”
Section: Introductionmentioning
confidence: 99%